Penguatan Kelembagaan Desa dalam Mewujudkan Otonomi di Desa-desa Pesisir: Studi di Desa Sokop Kecamatan Rangsang Pesisir Kabupaten Kepulauan Meranti - M. Tinov; Tito Handoko (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This study examines the institutional strengthening Sokop village in the district of Meranti Islands. The village of institutional issues Sokop be a reflection of the condition of the villages are located in coastal areas and outer islands in Indonesia. Limitations accessibility of information, transport and communication are key issues faced by the region (read-Village Sokop) so that the development of institutional capacity and its derivatives is not as advanced and as fast as the accessibility of the region are within easy reach. By putting itself on the theoretical framework of institutional strengthening these studies focus to see phenomena institutional Village Sokop especially from the aspect of good governance and administrative capacity Sokop Village Government officials. This study used a qualitative approach and to optimize the study, the authors used the strategy phenomenology. The results of this study indicate that the institutional capacity of the village government Sokop not support in efforts to achieve regional autonomy, it is characterized by weak institutional role Desa Sokop in building independence of the village, institutional structuring and management of village governance, weak financial management, and lack of community participation in development village (participatory development).